"Inter-Longitude Astronomy" project: long period variable stars - Andronov, I.L.; Marsakova, V.I.; Kudashkina, L.S.; Chinarova, L.L. (Advances in Astronomy and Space Physics, 2014)
This article contains the highlights of complex studies of long-period variable stars such as Miras: semiregular, symbiotic (particularly, pulsating symbiotic), as well as RV Tauri-type stars. In the course of these studies, important characteristics of mean light curves were determined. In the case of multi-component variability, additional periods were found. Correlations between parameters of mean light curves were investigated. The cycle-to-cycle changes of light curve parameters were analysed using various mathematical methods. Classification criteria of variable stars and effects of variability were proposed based on this research. The study of observational parameters and the correlations between them can be used to estimate the age, mass, and other physical characteristics of AGB stars.